What Motivates Teachers to Stay Faithful to the Teaching Profession? - Carls, Kathryn Medina (International Multidisciplinary Research Journal, 2020)
This descriptive research inquired on the motivational factors that made teachers stay faithful to the teaching profession. There were 18 teacher–participants from the public and private basic education and secondary school of the City Schools of Dasmarinas. The qualitative part was done through triangulation and was participated by 18 teachers or significant others whose responses shed light on the prime question: ”what made teachers stay faithful to the teaching profession” asked through- narrative inquiry. However, in the journey of searching for the best motivational factors, some weak areas were discovered that paved the way to the formulation of an effective framework of analysis that would help address the not so strong points that hamper teaching effectiveness. Findings revealed that as to personal attributes, the teacher-participants served their schools for more than 6 years; working at their best always; recognition and prestige matters a lot for them; remuneration/ and other benefits were essential for them and equally important was, whatever they will be getting after retirement; with very satisfactory teaching performance; undoubtedly satisfied of the teaching profession, and did find teaching as a stable job. Conversely, there were some factors that teacher-participants were not so happy about and so the framework of analysis was formulated striking the balance between the strong and weak points. The framework has a universal C that stands for competence. C serves as the overall environment of the school with the strong motivational factors under its umbrella that must be sustained/fostered for the teachers to stay faithful to the teaching profession such as prestige and recognition; accountability and remuneration and other benefits. For the teacher-participants, these factors were all significant. The same factors motivated them to stay dedicated to the teaching profession. However, there were found motivational factors considered weak points that hamper teaching effectiveness and forwarded the following recommendations: (a) strengthen the policy on workload reduction and preparation time for learning materials hence, reduce stress; (b) provision for recreational activities that can foster greater camaraderie among employees; (c) provision for a more objective criteria on selection of teachers to participate in seminars funded by the school which must be related to the discipline they teach; (d) review seminar re-echo policy; offer strategic career development plans deemed needed for teachers’ continual improvement; and (e) provision for scholarships programs that can further enhance the potentials of teachers. Toward the end, this study hopes to open doors of improvement and encouragement that could add more flavor to the noblest profession.